Amylase-Arbitrated Antibiofilm and Anti-Biocorrosion Efficacy of Curcuma zanthorrhiza against Pseudomonas aeruginosa - Joseph, Delna; Vadakkan, Kayeen; Mani, Bince; Cheruvathur, Meena Kochappan (Asian Journal of Biological and Life Sciences, 2025)
Background: The current research explores the antibiofilm and anti-corrosive effects of the hydromethanolic extract of the Curcuma zanthorrhiza rhizome. Biofilm-mediated infections are prevalent and can result in periodontal infection, adenotonsillar hypertrophy, chronic rhinosinusitis, prosthetic joint infection, medical device-related infections, etc. The emergence of biofilms on a metal substrate triggers biocorrosion, and it results in the collapse of buildings and bridges, chemical and oil pipeline breakage, etc. As various bacteria acquired antibiotic resistance to synthetic drugs, it is high time to introduce the antibiofilm and anti-biocorrosive potential of Curcuma zanthorrhiza rhizome extract. Materials and Methods: The potential of the hydro-methanolic crude extract of Curcuma zanthorrhiza against Pseudomonas aeruginosa biofilm was evaluated by a microtiter plate assay. Scanning electron microscopic evaluation and EtBr/AO fluorescence assay were also performed. Results: Treatment with 40 mg/mL of Curcuma zanthorrhiza extract resulted in biofilm inhibition of about 56%. Fluorescence microscopy was used to assess the biofilm inhibition by EtBr/AO staining in Pseudomonas aeruginosa. Extract-treated cells appeared in a yellow to orange color, and their cytoplasmic membrane integrity was seen to be lost. Scanning electron microscopy images of the surface morphology evaluation revealed the remarkable biocorrosion inhibition of Curcuma zanthorrhiza. Invaginations and grooves in the surface of plant extract-treated steel coupons were minor in comparison with untreated samples. Enzyme kinetics assessment validated the amylase-mediated action of plant extracts in inhibiting biofilm and biocorrosion. Conclusion: Analysis of spectrophotometric data revealed the amylase-mediated anti-biofilm and anti-biocorrosion activity of Curcuma zanthorrhiza.
Keywords: Biocorrosion; Biofilm; Curcuma zanthorrhiza; Pseudomonas aeruginosa; Zingiberaceae